Urinary tract infection in elderly: clinical profile and outcome study done at Kempegowda Institute of Medical Science and Hospital, Bengaluru, India - Swamy, Sumedha; Ramaswamy, Manjunath; Pakale, Ashootosh M. (International Journal of Research in Medical Sciences, 2018)
Background: Urinary tract infection (UTI) being the most common bacterial infection with considerable morbidity and mortality. In hospitalized geriatric patients, the risk is more attributable to differing characteristics such as anatomical and hormonal changes, presence of comorbidities such as neurological and urological abnormalities, diabetes mellitus and prolonged indwelling catheter use in hospitals and long-term care facilities. Methods: A retrospective study of patients admitted to medicine wards of age above 60 years with symptoms of urinary tract infection and positive urine culture spanning over a year were included. Demographic profile, clinical features, predisposing factors, laboratory features, urine culture reports, antimicrobial susceptibility patterns and outcome were noted and analysed. Results: Of the 120 patients included in our study, 58.2% were males and 41.8% were females. Dysuria was the most common major symptom (77.5%). Diabetes mellitus was the most common Predisposing factor observed in (63.3%) of the patients. Gram negative organism were responsible for (68.27%) of the uropathogen profile; Escherichia coli was the commonest isolate (31.66%) seen. Mortality rate was 29.16%. Significantly higher mortality was seen in patients with diabetes mellitus (p<0.001), complicated UTI (p<0.001), serum creatinine >1.4mg/dl (p<0.001) and increasing number of predisposing factors. Mortality was also associated with higher leucocyte count in the study population. Conclusions: Urinary tract infection in elderly increases the population mortality and morbidity; and the co morbid factors associated play a key role in the severity of the infection. Early management and appropriate antibiotic therapy will help in preventing antibiotic resistance and also in decreasing the overall geriatric population fatality.